(untitled) (CIPEEX, 2025)
This paper examines the validity of completing the statutory minimum of fifteen jurors, on the trial day, by drawing alternates from another panel of the same Jury Court and whether such practice entails nullity. It is a doctrinal and case-law review with a normative analysis of the Code of Criminal Procedure and higher-court precedents, aimed at systematizing validity criteria and the proper timing for objections. The aim is to show under which conditions this practice—used to avoid adjournment—preserves the composition of the Jury and complies with procedural rules. The method consisted of a critical reading of textbooks and rulings, emphasizing the installation of the session, the minutes recording the presence of at least fifteen jurors, and the parties’ conduct regarding consent or the absence of a timely challenge. The findings indicate a consolidated understanding that calling alternates from another panel within the same Jury Court, with the parties’ awareness, does not amount to nullity; any objection must be raised immediately, on pain of preclusion. It concludes that the measure is consistent with the procedure’s purpose, provided that adversarial guarantees are observed and the act is duly recorded in the case file.